Will digital technologies transform agriculture in developing countries?. (November 2016) - Deichmann, Uwe; Goyal, Aparajita; Mishra, Deepak
Abstract: Mobile phones and the internet have significantly affected practically all sectors of the economy and agriculture is no exception. Building on a recent World Bank flagship report, this article introduces a concise framework for describing the main benefits from new information and communication technologies. They promote greater inclusion in the broader economy, raise efficiency by complementing other production factors, and foster innovation by dramatically reducing transaction costs. The article reviews the recent literature on corresponding technology impacts in the rural sector in developing countries. Digital technologies overcome information problems that hinder market access for many small‐scale farmers, increase knowledge through new ways of providing extension services, and they provide novel ways for improving agricultural supply chain management. While there are many promising examples of positive impacts on rural livelihoods—or "digital dividends"—these have often not scaled up to the extent expected. The main reason is that technology can always only address some, but not all of the barriers faced by farmers in poorer countries.